Representing the "European refugee crisis" in Germany and beyond: Deservingness and difference, life and death - HOLMES, SETH M.; CASTAÑEDA, HEIDE (American ethnologist, 2016)
ABSTRACT The European refugee crisis has gained worldwide attention with daily media coverage both in and outside Germany. Representations of refugees in media and political discourse in relation to Germany participate in a Gramscian “war of position” over symbols, policies, and, ultimately, social and material resources, with potentially fatal consequences. These representations shift blame from historical, political‐economic structures to the displaced people themselves. They demarcate the “deserving” refugee from the “undeserving” migrant and play into fear of cultural, religious, and ethnic difference in the midst of increasing anxiety and precarity for many in Europe. Comparative perspectives suggest that anthropology can play an important role in analyzing these phenomena, highlighting sites of contestation, imagining alternatives, and working toward them. [refugee, media, immigration, crisis, Germany, Europe]